Pencegahan Stunting Dengan Camilan Kaya Kalsium Sebagai Makanan Tambahan Anak Balita di Desa Borisallo, Kec. Parangloe, Kab. Gowa - Wardiah Hamzah; Nasruddin Syam (ASPIRASI : Publikasi Hasil Pengabdian dan Kegiatan Masyarakat, 2024)
Increased food production requires fertilizers and pesticides. Fertilizers are used to increase soil fertility and pesticides are used to eradicate pests in food crops and plantations. Problems of farmers in Pucak Village, Kec. Tompobulu as a partner does not know the level of exposure to pesticides, does not know the impact of pesticides on health problems and does not have Personal Protective Equipment (PPE) when spraying. The solutions are: (1) Counseling on prevention and the impact of the use of fertilizers and pesticides on the incidence of dermatitis, (2) Provision of PPE in the form of masks and gloves in fertilizing and spraying pesticides. The results of community service are (1) Counseling on prevention and the impact of using fertilizers and pesticides on the incidence of dermatitis, which is carried out by conducting home visits. Farmers experienced an average increase in knowledge of safe and healthy fertilizing and pesticide spraying management, (2) Provision of PPE, especially hats, masks and gloves to farmers. Abstract: Increasing food production requires fertilizer and pesticides. Fertilizer is used to increase soil fertility. Fertilizer has a negative impact in the form of disease and poisoning on farmers in Borisallo Village, Kec. Parangloe, Kab. Gowa as a partner does not yet know how to prevent exposure to organic fertilizers on health, there is no provision of micronutrient supplementation (Calcium, Magnesium, Zinc, Boron and Vitamin D) as an increase in body immunity and detoxification of fertilizer exposure poisoning and there is no availability of Personal Protective Equipment in managing fertilizers in the form of masks and gloves for farmers. The solutions are: (1) Counseling on preventing fertilizer exposure to farmers, (2) Providing micronutrient supplementation (Calcium, Magnesium, Zinc, Boron and Vitamin D) to increase body immunity and detoxify fertilizer poisons, (3) Providing Personal Protective Equipment (PPE) in the form of masks and gloves when carrying out inorganic fertilization on farmers. The results of community service are (1) Counseling on prevention and the impact of using organic fertilizer on health, which is carried out by conducting home visits. Farmers experienced an average increase in knowledge of safe and healthy management of fertilization and pesticide spraying, (2) providing micronutrients and explaining sources of other food ingredients containing micronutrients in their environment, (3) Providing PPE, especially hats, masks and gloves to farmers